PENGEMBANGAN PENDIDIKAN DI PAPUA : PERSPEKTIF AGAMA DAN PERUBAHAN SOSIAL - Paulus Satyo Istandar Tan (SOSCIED, 2019)
Without Education a person can learn from the environment (natural and social) so that his experience accumulates, and the person will have certain skills. But with education, learning efforts will become more efficient and effective, especially if guided by teachers and supported by the experiences of others (references). So on this good occasion in seeing the development of education in the Land of Papua, we need to look also from the perspective of religion and social change The research method used is a qualitative description method by collecting library data, reading and recording and processing research materials. May one appropriate step be pursued in the development of Education in the Land of Papua by taking into account religious views and social change is "Autonomization of Education".